An Eighteenth Dynasty Writing Board (Ashmolean 1948.91) and The Hymn to the Nile - Hagen, Fredrik.
The article presents a writing tablet from the Ashmolean Museum, Oxford. It contains various administrative accounts as well as one of the earliest-known copies, in duplicate, of the initial lines of The Hymn to the Nile, written by different hands, probably made by a teacher and his student. The variants of the two copies are compared and analysed, and the use of writing boards in New Kingdom Egypt is outlined. Finally, the social context of the hymn is discussed.